Genome-wide association and genomic selection in aquaculture - José M. Yáñez; Agustín Barría; María E. Lopez; Thomas Moen; Baltasar F. Garcia; Grazyella M. Yoshida; Peng Xu (John wiley & Sons Australia, Ltd., 2025)
Recent advancements in genomic technologies have led to the discovery and application of DNA-markers [e.g. single nucleotide polymorphisms (SNPs)] for the genetic improvement of several aquaculture species. The identification of specific genomic regions associated with economically important traits, using, for example, genome-wide association studies (GWAS), has allowed the discovery and incorporation of markers linked to quantitative trait loci (QTL) into aquaculture breeding programs through marker-assisted selection (MAS). However, most of the traits of economic relevance are expected to be controlled by many QTLs, each one explaining only a small proportion of the genetic variation. For traits under polygenic control, prediction of the genetic merit of animals based on the sum of effects at positions across the entire genome (i.e. genomic estimated breeding values, GEBV, which are used for what has become known as genomic selection), has been demonstrated to speed the rate of genetic gain for several traits in aquaculture breeding. The aim of this review was to provide an overview of the development and application of genomic technologies in uncovering the genetic basis of complex traits and accelerating the genetic progress in aquaculture species, as well as providing future perspectives about the deployment of novel molecular technologies for selective breeding in coming years.